MODIFIKASI METODE NEWTON DENGAN KEKONVERGENAN ORDE EMPAT - Yenni May Sovia; Agusni '; Supriadi Putra (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses the modiﬁcation of Newton’s method using a slope-line approximate in a form of quadratic polynomial to solve a nonlinear equation. This iterative method has a convergence of fourth order and for each iteration, it requires three function evaluations, so the eﬃciency index of the method is 1.587, which isbetter than that of the Newton’s method, which is 1.414. Furthermore, the computational tests show that proposed method is superior to the Newton’s method in terms of speed to obtain a root.